Draping in Dermatology: A Patient's Perspective. Issue 6 (November 2022) - Cyr, Janelle; Choi, Bohmyi; Melkis, Justina; Gresham, Louise; Huang, Christina M.; Beecker, Jennifer
Background/Objectives: Patient dignity is a core component of the Canadian health care system; however, there may be challenges to maintaining patient dignity in clinical settings requiring total body skin examination (TBSE) for adequate assessment and diagnosis. As standardized TBSE draping practices have not been investigated in a dermatology setting, we sought out to investigate subjective patient experiences of draping practices. Methods: A cross-sectional study was performed using a paper survey in dermatology hospital clinics over a 6-month period to 150 patients. Results: Draping was considered important by over 50% of patients surveyed (54.7%). Respondents who indicated that draping impacted their comfort level "a lot" or "very much" had a mean age of 52 and were more likely to be females ( P < .05). Females were also more likely to answer that their body weight/shape ( P < .05), physician of same ( P < .01) or opposite sex ( P < .001), and the degree of privacy offered by drapes ( P < .001) impacted their comfort level when undressing for a TBSE. Respondents who reported that any assessed factor impacted their comfort during a TBSE were also younger ( P < .05), suggesting that younger and female patients were more likely to have comfort concerns than males. Conclusions: Our study confirmed that most patients surveyed considered draping to be important. Our findings highlight the importance of adequate draping practices to maintain patient privacy and dignity for all patients, with special attention to younger female patients to ensure they feel as comfortable as possible. Future research should focus on how these identified patient comfort factors can be implemented into medical education.